2013
DOI: 10.1089/tmj.2012.0154
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Telemedical Service Centers in Managing Remote Monitoring Data Transmitted Daily by Cardiac Implantable Electronic Devices: Results of the Early Detection of Cardiovascular Events in Device Patients with Heart Failure (detecT-Pilot) Study

Abstract: The TmSC-based management concept was well accepted and appreciated by the majority of physicians and patients. It may be helpful in gaining symptomatic information on top of automatic HM data and in supporting smaller clinics in the follow-up of their device patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…23 26 28 30 32 38 39 Experiences of patient-provider communication, 24 25 27 28 31 32 36 relationships 23 27 28 30 32 33 36 as well as patient empowerment, 24 25 27 30 36 38 39 were addressed in seven of the 18 studies, thus focusing on relational aspects of experiences, while coordination and continuity of care were reported in one-third of studies, 26 28 29 31 32 36 reflecting a focus on the organisational dimensions of HCX. Little research explored experiences with emotional or physical support, 30 32 38 the integration of medical and non-medical care, 31 essential characteristics of the provider, 27 28 patient perceptions of being a unique person 27 and the involvement of family and friends. 38 No study investigated experiences of patients with teamwork and teambuilding of healthcare providers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 26 28 30 32 38 39 Experiences of patient-provider communication, 24 25 27 28 31 32 36 relationships 23 27 28 30 32 33 36 as well as patient empowerment, 24 25 27 30 36 38 39 were addressed in seven of the 18 studies, thus focusing on relational aspects of experiences, while coordination and continuity of care were reported in one-third of studies, 26 28 29 31 32 36 reflecting a focus on the organisational dimensions of HCX. Little research explored experiences with emotional or physical support, 30 32 38 the integration of medical and non-medical care, 31 essential characteristics of the provider, 27 28 patient perceptions of being a unique person 27 and the involvement of family and friends. 38 No study investigated experiences of patients with teamwork and teambuilding of healthcare providers.…”
Section: Resultsmentioning
confidence: 99%
“…Little research activity was observed for HCX with emergency care services, 28 allied healthcare, 26 32 33 35 long-term care (1/18 studies), 28 mental healthcare (2/18 studies), 31 35 psychosocial healthcare (3/18 studies) 26 31 32 and telemedical care. 30 No research investigated HCX with public health, disease management programmes and complementary and complementary medicine. Qualitative studies covered the widest range of healthcare services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 9 The goals are to improve the quality of care for the patients and increase efficiency for the healthcare providers. 2 4 , 9 , 10 , 13 17 The medical benefit of remote monitoring has been increasingly substantiated by randomized, controlled clinical trials, such as TRUST, 10 CONNECT, 14 COMPAS, 18 and EVOLVO. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Die Dienstleistung ergänzt die medizinische Versorgung durch den Arzt. Studien haben gezeigt, dass durch die Übernahme delegierbarer Leistungen der Arbeitsaufwand seitens der Ärzte reduziert werden kann[6]. Den größten Vorteil eines externen Dienstleisters sehen die Befragten in der Möglichkeit, optimale Servicezeiten abzudecken sowie in der hohen Ressourceneffizienz bei der Erbringung der Leistung.…”
unclassified